Training on investment in upgraded milling technologies in West Africa - CGIAR Research Program on Rice (2019)
Research showed upgraded millers in West Africa faces challenges, notably in terms of paddy collection, agricultural financing and scale of activity The innovation consists in a training for millers to address these issues. It is at a stage of “first idea”, which must be developed by partners.